How self-leadership promotes job crafting: Based on the perspective of self-determination theory - Liu, Geng; Peng, Huimin; Wen, Hao (Frontiers in Psychology, 2023)
Based on self-determination theory, the present study develops a moderated mediation model to investigate how and when self-leadership promotes employees’ job crafting, highlighting the mediating role of autonomous motivation and the moderating role of leader empowering behavior. We test the hypotheses based on valid data collected from 269 employees using a three-wave longitudinal study design. The results show that self-leadership has a significantly positive effect on job crafting, and a positive indirect effect on job crafting via autonomous motivation. Furthermore, leader empowering behavior not only enhances the positive impact of self-leadership on autonomous motivation, but also positively moderates the mediating role of autonomous motivation in the relationship between self-leadership and job crafting. Practically, our study provides insights into how to promote job crafting. We also propose limitations and directions for future research.